Longitudinal variations of the ionospheric trough position. Issue 2 (15th January 2019) - Karpachev, A.T.; Klimenko, M.V.; Klimenko, V.V.
Highlights: Longitudinal variation in the ionospheric trough position are studied. The Interkosmos-19, Kosmos-900 and CHAMP data are used. All the local time hours, the Northern and Southern hemispheres are considered. The winter conditions at low and high solar activity are discussed. Abstract: For the first time a comprehensive pattern of the longitudinal effect of the ionospheric trough position was obtained. We present new results with longitudinal variations of the winter trough position as a function of geomagnetic latitude for both hemispheres and conditions of high and low solar activity and all local time hours. We used a large observational data set obtained onboard the Kosmos-900, Interkosmos-19 and CHAMP satellites for quiet geomagnetic conditions. We found that a magnitude of the trough position longitudinal effect averaged for a fixed local time is greater in the daytime (6–8°) than in the nighttime (3–5°). The longitudinal effect magnitude reaches its maximum (16°) in the morning (at 08 LT) in the Southern hemisphere at high solar activity. But on certain days at any solar activity the longitudinal effect magnitude can reach 9–10° even at night. The shape of the longitudinal effect was found to differ significantly in two hemispheres. In the Northern hemisphere the trough is usually closest to the pole in the eastern (American) longitudinal sector, and in the Southern hemisphere the trough is closest in the western (Eurasian) longitudinal sector. The magnitude and shape of the longitudinal effect is also different during low and high solar activity. The Global Self-consistent Model of the Thermosphere, Ionosphere, and Protonosphere (GSM TIP) simulations demonstrate that during low solar activity, the longitudinal variations of the daytime trough position is mainly determined by longitudinal variations of the ionization function, formed due to the longitudinal variations in the solar zenith angle and the atomic oxygen density distribution. The longitudinal variations of the nighttime trough position is formed by the longitudinal variations in ionization of precipitating auroral particles, neutral atmosphere composition, and electric field.